Identification of Edible Fish Species of Pakistan Through DNA Barcoding - Ghouri, Muhammad Zubair; Ismail, Muhammad; Javed, Muhammad Asif; Khan, Sultan Habibullah; Munawar, Nayla; Umar, Abdullah Bin; Mehr-un-Nisa,; Aftab, Syed Ovais; Amin, Shazia; Khan, Zulqurnain; Ahmad, Aftab (Frontiers in Marine Science, 2020)
Fish is a fundamentally healthy food, loaded with essential nutrients, high protein content, vitamin D, and omega-three fatty acid. Mislabeling is a common problem in the fish industry that causes an imbalance in prices and fluctuation in the market. DNA barcoding is a potential technique for authentication of mislabeled and misidentified fish species. In this study, 11 freshwater and 6 marine fish species were used for DNA barcoding and further authentication using the mitochondrial cytochrome b (Cyto b) gene. Cyto b was amplified using PCR, producing an average read length of 1,141 bp. The obtained sequences were compared to the National Center for Biotechnology Information database using the Basic Local Alignment Search Tool. The average AT content (55.20%) was higher than the average GC content (44.78%) in marine and freshwater fish species. The mean genetic Kimura 2-parameter distances for species, genus, families, and orders were 0.311, 0.308, 0.023, and 0.337, respectively. Phylogenetic tree analysis revealed that most of the freshwater fish species clustered together due to the fact that they were in the same order or family, while the marine fish species clustered distantly. Single nucleotide polymorphism (SNP) analysis of all species in the study revealed distinct features regarding unique sites. All fish species could be identified based on their unique SNP profiles. Based on SNP data, DNA sequence based QR codes were developed for accurate identification of fish species. This is the first study to develop DNA-based QR barcodes for proper authentication of species during the chain of custody using simple technology.